2011
DOI: 10.3111/13696998.2011.630850
|View full text |Cite
|
Sign up to set email alerts
|

The STARRT trial: a cost comparison of optimal vs sub-optimal initiation of dialysis in Canada

Abstract: The results of this study indicate, after adjusting for potential confounders, that optimally initiated patients for RRT have significantly lower healthcare-associated costs compared to sub-optimally initiated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Canadian data showed that the average total cost per patient was an estimated $63,225 for the suboptimally initiated patients and $39,260 for the optimally (dialysis initiation as an outpatient, using arteriovenous fistula, graft, or PD catheter) initiated patient 37. Most developed countries can provide PD at lesser expense to the health care system than HD 18.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian data showed that the average total cost per patient was an estimated $63,225 for the suboptimally initiated patients and $39,260 for the optimally (dialysis initiation as an outpatient, using arteriovenous fistula, graft, or PD catheter) initiated patient 37. Most developed countries can provide PD at lesser expense to the health care system than HD 18.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that UPS bears several disadvantages: besides an increased mortality and hospitalization rates, higher total costs have been recorded [4-6]. …”
Section: Introductionmentioning
confidence: 99%
“…on a nonpreferred modality, with a nonpreferred access, or in hospital). 9 Cost estimates for optimal and suboptimal initiation of dialysis were taken from a multicenter retrospective study, and totaled $54,679 for patients who experience suboptimal dialysis initiations and $33,953 for optimally initiated patients. 9 The cost of a hospitalization event was assumed to be $11,640 based on estimates from the Agency for Healthcare Research and Quality.…”
Section: Methodsmentioning
confidence: 99%
“…8 Unfortunately, even among patients followed by a nephrologist and multidisciplinary care team, 50% or more experience a suboptimal initiation of dialysis. 9,10 Moreover, more than half of dialysis initiations involve a hospitalization or emergency department visit due to severe uremic symptoms, volume overload, or hyperkalemia. 7 Initiating dialysis earlier at a higher kidney function before patients are symptomatic and when there is less risk of suboptimal starts is not an ideal solution, as it increases health care costs without a clinical benefit.…”
mentioning
confidence: 99%